Non-stationary processes in oil-product pipeline using anti-turbulence additives - Grudz, V. V.; Al-Dandal, R. S. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2015)
The problem of a non-stationary flow of petroleum products by the pipeline in the process of its displacement by antiturbulence additives is studied in the article. There is made a mathematical model of motion of a contact for two liquid media with different hydraulic characteristics in the pipeline. The model implementation allows predicting the type of motion of the moving boundary, pressure distribution and flow of petroleum products during the process of non-stationary displacement. It is determined that oscillation of parameters in time is negligible, and it allows recommending the quasistationary motion models for predictive calculations